Therapy Approaches in Neurological Disorders - Bernardo-Filho, Mario; Taiar, Redha; da Cunha de Sá-Caputo, Danúbia; Seixas, Adérito (IntechOpen, 2021)
Neurological disorders are conditions affecting the central or peripheral nervous system, with undesirable consequences for the quality of life. This book highlights and discusses several approaches for managing these conditions and improving the functional capacity and quality of life of patients, including whole-body vibration exercise, biofeedback, sagittal plane spine alignment, allopathic and non-allopathic medications, phytotherapy, and more.